A educação ambiental crítica e a formação humana: a tomada de consciência e a elaboração conceitual na formação de educadores ambientais - Costa, Lorenna Silva Oliveira (2017)
The understanding of the learning processes foundations of environmental concepts in Science teachers‟ initial formation is an important point to take into consideration in the capabilities of Critical Environmental Education (EAC). In this context, the research problem of the present work was: how does the relation between the environmental knowledge appropriation and human formation, in the act of knowing, in a specific educational space occur? We sought to investigate how the teaching of environmental concepts, in a dialectical approach, can contribute to the students‟ awareness and their conceptual elaboration, in a specific context of school education, and, thus, elaborate new understandings of these processes. The methodological and epistemological positions of this research were grounded, mainly, on Historical-Dialectical Materialism and Historical-Cultural Theory. A theoretical study was carried out concerning: 1) the core determinations of the environmental crisis‟s instauration, regarding it as a historical process; 2) the historical and dialectical perspective of the relation between society and nature; 3) the human formation elements, focused on the development of Higher Psychological Functions, in particular the conceptual formation and awareness; and 4) the Environmental Education as a political Education and as an element for human formation aimed at questioning and transforming reality. Along with this study, an empirical research was carried out with students from a Chemistry graduation course in the Center-West region of Brazil, linked to a Chemistry sub-project of the Institutional Program of Teaching Initiation Scholarships (PIBID). The Pedagogical Project of the Course was previously analyzed in order to investigate the possible presence of environmental contents and, through questionnaires, the subjects‟ environmental concepts and the aspects of their experiences were identified. Subsequently, we analyzed the conceptual formation and the evidences of awareness of these subjects over a semester, in a Discussion Group which held 14 meetings. The meetings were filmed, transcribed and analyzed using Micro-genetic Analysis, based on Lev Vygotsky. Through the analyses, four categories, which involve the environmental concepts discussed were elaborated: 1) the view of what environment is; 2) the explanations about the environmental crisis; 3) the motivations and educational instances in the formation of the environmental educator; and 4) the me-other view in the world and the neoliberal rationality. After this elaboration, two indicators of the meaning-sense relation that comprise affective and intellectual elements were identified: 1) affective expressions and; 2) concept generality relations. Such indicators came up, implicitly or explicitly, in the enunciations of all categories. To those indicators were elaborated sub-indicators. It was observed that the concepts most mobilized by students were those constructed in other educational instances such as the church and the media, which reflected little school Education influence. The students presented a fragmented view that did not regard the human being as a form of nature existence. The discussions demonstrated limitations in the relations of their conceptual networks, with little amplitude in the degrees of generality. Since the EAC questioned many meanings that were stable for students, we observed their backlash against some of the concepts /themes, which resulted in the students‟ resistance to learning them. The verbal students‟ interventions were predominantly grounded on a network of spontaneous concepts based on a neoliberal project of society. On the other hand, it was possible to note the importance and formative potentiality of studying time and dialogues prompted to broaden students' conceptual network, denaturalize socio-environmental relations and contribute to the reflection process and appropriation of scientific concepts.